Patient-Reported Functional and Satisfaction Outcomes after Robotic-Arm-Assisted Total Knee Arthroplasty: Early Results of a Prospective Multicenter Investigation - Khlopas, Anton; Sodhi, Nipun; Hozack, William J.; Chen, Antonia F.; Mahoney, Ormonde M.; Kinsey, Tracy; Orozco, Fabio; Mont, Michael A. (The Journal of Knee Surgery, 2020)
The purpose of this study was to perform a 3-month interim comparative analysis on outcomes between robotic-arm-assisted total knee arthroplasty (RATKA) and manual TKA patients. Specifically, we evaluated (1) patient self-reported symptoms, (2) expectations and satisfaction, and (3) functional activities, based on the 2011 Knee Society Scoring System. Between June 1, 2016, and March 31, 2018, 252 patients (102 manual and 150 robotic) were enrolled into a prospective, nonrandomized, open-label, multicenter comparative cohort study. Functional activity scores, patient-reported symptoms, as well as satisfaction and expectation scores were obtained from the 2011 Knee Society Scoring System preoperatively, at 4 to 6 weeks, and at 3 months postoperatively. Student's t-tests, Wilcoxon rank-sum tests, and chi-square tests with α set at 0.05 were used to compare between-group mean improvements from baseline. At 4 to 6 weeks postoperatively, RATKA patients were found to have significantly larger improvements in walking and standing (1.4 vs. –1.2 points; p = 0.019). RATKA patients were also found to have larger improvements in advanced activities (1.3 vs. 2.3 points), pain with walking (3.3 vs. 3.2 points), satisfaction score (12.4 vs. 12 points), and expectations score (5.1 vs. 4.4 points) when compared with manual TKA patients. At 3 months, RATKA patients were also found to have larger improvements in walking and standing (6.0 vs. 4.8 points), standard activities (11.4 vs. 10.1 points), advanced activities (6.2 vs. 4.6 points), functional activities total score (22.8 vs. 21.2 points), pain with walking (4.3 vs. 4.1 points), total symptoms score (10.5 vs. 10.3 points), satisfaction score (17.0 vs. 15.5 points), expectations score (4.8 vs. 4.0 points) when compared with manual TKA patients. The data indicate RATKA patients to have equal or greater improvements in 9 out of 10 of the Knee Society Scoring System components assessed at 3 months postoperatively, though not all findings were statistically significant. Since this is an early results report, this study will be continued for a longer follow-up, but we are encouraged by these interim results.
Keywords: robotic-arm-assisted; total knee arthroplasty; patient satisfaction; outcomes; surgical technology